Managerial statistics abbeviated - Keller, Gerald (South-Western /Cengage Learning, 2009)
This book is about data collection and sampling, probability, analysis of variance, introduction to estimation, introduction to hypothesis testing, inference about population, simple linear regression and correlation, Chi-Squared tests and multiple regression.